2021
DOI: 10.1097/md.0000000000024664
|View full text |Cite
|
Sign up to set email alerts
|

The effect of pretreatment BMI on the prognosis and serum immune cells in advanced LSCC patients who received ICI therapy

Abstract: This study aims to evaluate the prognosis and serum immune cells of patients with different pretreatment body mass index (BMI) values. The data of 61 newly diagnosed patients with advanced lung squamous cell carcinoma (LSCC) who received immune checkpoint inhibitors (ICIs) combined with chemotherapy were obtained from the database of Rizhao People's Hospital (Rizhao, Shandong). According to the cutoff value of BMI (23.2 kg/m2), 32 patients had a high BMI and the remaining 29 patients had a low BMI. The effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…White adipose tissue serves as a reservoir for memory T cells, facilitating rapid response to exogenous stimuli [16,17]. Additionally, alterations in body composition have a negative impact on the activity of immune cells [18] Wang et al demonstrated that patients with a higher BMI have a well-developed immune system and can mobilize more immune cells [19]. In contrast, endstage tumor patients with wasting conditions (BMI < 18.5 kg/m²), mainly due to malnutrition or cachexia, exhibit suppressed immune cell activity, including CD8 + T and CD4 + T. [20] CD4 + T cells, also known as helper T cells, primarily secrete cytokines to regulate the function of other immune cells.…”
Section: Discussionmentioning
confidence: 99%
“…White adipose tissue serves as a reservoir for memory T cells, facilitating rapid response to exogenous stimuli [16,17]. Additionally, alterations in body composition have a negative impact on the activity of immune cells [18] Wang et al demonstrated that patients with a higher BMI have a well-developed immune system and can mobilize more immune cells [19]. In contrast, endstage tumor patients with wasting conditions (BMI < 18.5 kg/m²), mainly due to malnutrition or cachexia, exhibit suppressed immune cell activity, including CD8 + T and CD4 + T. [20] CD4 + T cells, also known as helper T cells, primarily secrete cytokines to regulate the function of other immune cells.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the outcomes of ICI therapy are invariably affected by obesity. In a cohort of 61 squamous cell carcinoma patients, Wang et al found a positive linear relationship between pre-treatment BMI and post-treatment blood immune cells, indicating a better response to immunotherapy in individuals with higher BMI ( 71 ). Better treatment response also correlated with better survival outcomes ( 71 ).…”
Section: Obesity and Therapeutic Survival Of Lung Cancermentioning
confidence: 99%
“…In a cohort of 61 squamous cell carcinoma patients, Wang et al found a positive linear relationship between pre-treatment BMI and post-treatment blood immune cells, indicating a better response to immunotherapy in individuals with higher BMI ( 71 ). Better treatment response also correlated with better survival outcomes ( 71 ). Many studies have found that higher BMI was significantly associated with better OS and PFS in patients treated with ICI ( 22 , 24 , 69 , 71 - 76 ) ( Table 4 ).…”
Section: Obesity and Therapeutic Survival Of Lung Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…[16] Some studies have shown that the different compositions and locations of tumor immune cells are closely related to the prognosis of LSCC. [17,18] However, in past studies, researchers used traditional methods, such as immunohistochemistry, to explore the composition of immune cells in malignant tumor tissues. The number of cells that these methods can detect is very limited.…”
Section: Introductionmentioning
confidence: 99%